2022
DOI: 10.3389/feart.2022.953805
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of vegetation responses to meteorological drought from both linear and nonlinear perspectives

Abstract: The frequent occurrence of drought events in recent years has caused significant changes in plant biodiversity. Understanding vegetation dynamics and their responses to climate change is of great significance to reveal the behaviour mechanism of terrestrial ecosystems. In this study, NDVI and SIF were used to evaluate the dynamic changes of vegetation in the Pearl River Basin (PRB). The relationship between vegetation and meteorological drought in the PRB was evaluated from both linear and nonlinear perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The NDVI data and land cover data used in this study were acquired from the Model Resolution Imaging Spectrometer (MODIS) [3]. The MODIS NDVI datasets (MOD13C2) offer a temporal resolution of 1 month and a spatial resolution of 0.05 • [11].…”
Section: Datasetsmentioning
confidence: 99%
See 3 more Smart Citations
“…The NDVI data and land cover data used in this study were acquired from the Model Resolution Imaging Spectrometer (MODIS) [3]. The MODIS NDVI datasets (MOD13C2) offer a temporal resolution of 1 month and a spatial resolution of 0.05 • [11].…”
Section: Datasetsmentioning
confidence: 99%
“…However, PWC is limited to excluding a single variable [40]. The improved PWC analysis enables the examination of wavelet coherence in the time-frequency domain after removing the effect of other factors [3]. For a more detailed description and calculation process of the improved PWC, please refer to the study conducted by Hu and Si [40].…”
Section: Partial Wavelet Coherencementioning
confidence: 99%
See 2 more Smart Citations
“…Because human activities and land cover could have complex mechanisms impacting drought propagation [61,70], we were not able to sufficiently analyze human activities and land cover in this study. Previous studies have shown that if more variables, such as temperature, evaporation, and soil moisture are taken into account when calculating the drought index, the drought characteristics will change [71,72]. In this study, the SPI, with the characteristics of multiple timescales and easy calculations, was selected to represent meteorological drought.…”
Section: Comparisons and Limitationsmentioning
confidence: 99%